Nilai-nilai Ketauhidan dalam Novel KKN di Desa Penari Karya Simpleman - Azzahra, Ninda (YASIN, 2023)
This research is entitled "The Values of Monotheism in the novel KKN in the Dancer Village by Simpleman." The background of this research is the deviations from monotheism that occur in the novel, where the people in the village still adhere to the beliefs of their former ancestors, such as giving offerings to supernatural beings and forming alliances with jinns. As we know that the purpose of the apostles sent was to invite to monotheism of Allah. The essence of the teachings of monotheism is summed up in a sentence "Laailaaha Illallah" which according to Islamic terms is "rejecting everything to be made a god and stipulating that only Allah has the right to be worshiped." The main problem of this research is to find out deviations from the values of monotheism contained in the novel and what are the values of monotheism in Simpleman's KKN novel in Desa Penari. This study aims to find out deviations from the values of monotheism and explore the values of monotheism that exist in literary works, especially the novel KKN in the Dancer Village by Simpleman. The research method used in this research is library research with a hermeneutic approach with the KKN novel in Penari Village as the primary source of this research. The data collection technique used is data collection and analysis technique used is content analysis. The results of this study indicate that in Simpleman's novel KKN in the Dancer Village there are values that contain elements of deviant beliefs such as: 1) giving offerings to supernatural beings, making virgin children as sacrifices, ignoring customs and prohibitions in the village, committing immorality on the spot sacred, to make a pact with the genie. And there are monotheism values that can be used as a basis for knowing monotheism for readers, such as: 2) Prayer, saying two sentences of creed, praying, believing in supernatural things, trust, istighfar, grateful, trustworthy, patient and sincere.